Negotiating penal hybridity: Time–space boundary-work in parole decision making - Dagan, Netanel (Theoretical criminology, 2023)
Drawn on qualitative findings from discretionary chairpersons of parole boards in Israel, the study aims to theorize parole decision making as time–space boundary-work. Parole decision-makers were found to act within a hybrid professional environment that requires them to process distinct, and possibly conflicting, penal values, competencies and orientations. In order to address their professional tensions, parole decision-makers constantly negotiate their time and space, and thereby their professional identity. First, the parole decision-makers perform temporal boundary-work—conceptualizing their work and identity through qualitative-expansive time. Second, they perform spatial boundary-work—conceptualizing their work and identity through either (a) judicial space or (b) therapeutic space. This time–space work is used both to span and demarcate their boundaries in relation to other penal actors and to increase their visibility and legitimacy.